Rare neuroendocrine tumor decades after bladder exstrophy repair with enterocystoplasty - Sabine Roux; Marie-Laurenc; Nicolas Merzeau; Stéphane Larré; Priscilla Leon (Elsevier, 2018)
Bladder exstrophy is associated with an increased risk of bladder cancer. Adenocarcinoma is the main histological type found in the bladder exstrophy, accounting for 95% of cases, whereas squamous cell carcinoma accounts for 3-5% cases. We present here the rare case of the development of a metastatic neuroendocrine tumor on a bladder exstrophy, 26 years after enterocystoplasty enlargement. We describe the presentation of the cancer and the results after treatment by surgery and chemotherapy. Keywords: Bladder exstrophy, Neuroendocrine carcinoma, Urinary bladder neoplasms